The Architect Syphilis assay for antibodies to Treponema pallidum: an automated screening assay with high sensitivity in primary syphilis. Issue 1 (12th September 2008) - Young, H; Pryde, J; Duncan, L; Dave, J
Abstract : Objectives: To determine the sensitivity and specificity of the Architect Syphilis Chemiluminescence Assay (CLIA): a new highly automated screening test for syphilis. Methods: To establish the sensitivity of the Architect Syphilis assay we tested 129 stored sera from serologically characterised cases of untreated syphilis. The sera were selected to contain a disproportionately high number of primary infections. There were 79 primary infections, 29 secondary infections, 9 early latent infections and 12 latent syphilis of unknown duration. To establish the specificity of the assay we tested 1107 sera that had been submitted for routine syphilis serology. Results: The Architect CLIA and the Treponema pallidum particle agglutination test (TPPA) were in total agreement for all untreated infection with sensitivity of 98.4%. This was significantly higher than the sensitivity of the Murex immune capture enzyme (ICE) immunoassay (86%, p<0.001), the IgM enzyme immunoassay (EIA) (86.8%, p<0.001) and the Venereal Disease Research Laboratory test (VDRL) (83.7%, p<0.001). The difference in the sensitivity of the Architect and ICE assays was entirely due to primary stage syphilis (97.5% vs 77.2%, p<0.001). Although the specificity of Architect CLIA was very high (99.1%, 1049/1059) it was significantly lower (p = 0.016) than that of the Murex ICE assay (99.9%). Conclusions: The Architect CLIA is significantly more sensitive than the Murex ICE screening assay in detecting primary syphilis but it is significantly less specific. Given the relatively high levels of early syphilis, we consider a small increase in the number of confirmatory tests required to exclude false-positive results is worthwhile to increase the detection of primary syphilis by 20%.